You are on page 1of 12

1.

1
Warm-up Practice:
A.
1. 1, 3, 5, 7; 19; 29

2. 5, 8, 11, 14; 32; 47

3. 3, 6, 11, 18; 102; 227

4. -2, 1, 6, 13; 97; 222

5. ½, 2/3, ¾, 4/5; 10/11; 15/16

6. 1/5, 1/3, 3/7, 1/2; 5/7; 15/19

7. 2, 3/2, 4/3, 5/4; 11/10; 16/15

8. 0, ½, 2/3, ¾; 9/10; 14/15

9. 0, ¼, 2/5, ½; ¾; 14/17

10. ¾, 4/5, 5/6, 6/7; 12/13; 17/18

11. -1, 2, -3, 4; 10; -15

12. -1, 2, -3, 4; 10; -15

B.
13. 32

14. 33

15. 208

16. 9/10

C.
17. An = 2n – 1

18. An = 2n

19. An =

20. An =

; An = 1 +

21. An = 3n – 2

22. An =

23. An = 2n x (-1)

n-1

;An = 2n x (-1)

n+1

25. An = -3n + 2
n

An =
; An = 1 –

24. An = 3n x (-1)^(n – 1);An = 3n x (-1)

n+1

26. An = -4n + 3
n/2

2

27. An = (√5) ; 5

28. An = n + n

D.
29. 63

30. 126

31. 43/10 or 4 3/10

32. 17/4, 4 1/4

33. -13/15

34. 5/12

E.
35. 2 + 4 + 6 + 8 + 10 + 12 = 42

36. 1 + 4 + 7 + 10 + 13 + 16 + 19 + 22 = 92

37. 0 + ½ + 2/3 + ¾ + 4/5 = 163/60; 2 43/60

38. 1 + 1 + 1 + 1 +1 = 5

39. -1 + 1 – 1 + 1 – 1 + 1 = 0

40. ½ + 1/3 + ¼ + 1/5 = 77/60;1 17/60

F.

(walang page 14. 2x. n 1 2 3 4 5 F1 + F2 + …. 1/x . 13. 1/x 2 3 4 5 6 42. 1/x . ∑ 12. 1.∑ 11. ∑ 5. 1/x . . – 3 4. 1/x . x . . Fn 1 2 6 15 40 Notice that: 1. ∑ 14. Powerplus A. ∑ 7. x 3 4 8 2 3 4 5 44. 2x . 25/x 46. . (x + 3) + (x + 3) + (x + 3) + (x + 3) – + – + 4 + + B. – + – + + – – + 7 2 6. (x + 1)² + (x + 1)³ + (x + 1) + (x + 1) + (x + 1) + (x + 1) 5. (x – 3) + (x – 4) + (x – 5) + (x – 6) 5 6 3. 4x . ∑ 3. 4x. x . 2. 3x . 2 is True. 1. x . ∑ 10. Fn = FnFn + 1 2 Fn + 2 – 1 1 2 4 7 12 FnFn + 1 1 2 6 15 40 + .2 41. ∑ ∑ C. . x . ∑ 4. x. 5x 5 45. (x + 1) + (x + 2) + (x + 3) + (x + 4) 4 2. ∑ 8. Fn = Fn + 2 – 1 2 2 2 F1 + F2 + …. Fn 1 2 4 7 12 2 2 F1 + F2 + …. 4/x . 6x. 10x 3 4 5 6 7 43. ∑ 6. 16/x . 9/x . F1 + F2 + …. 1/x. a. na ulit yung 13) D. 1/x . 8x. ∑ 2. ∑ 9. x.

Similarly. 2 Next. but Fa + 2 + Fa + 3 = Fn + 4 . since n is odd. 2 = 1(3) + 1. 3. for n = 1. 13 + 14 + 15 + 16 + 17. We can denote that as: 2 n+1= F n FnFn + 2 + (– 1) . the equation will have + 1 when n is even and –1 when n is odd. where n is a positive integer. So. 5.3 + 4 + 5 + 6 + 7 + 8 + 9 + 10 + 11 + 12) 7747 1 5 10 . We know that n + 3 is even. . F a + 2 = FaFa + 3 2 – 1. => F n + 3 = Fn + 2Fn + 4 – 1.Fn + 1Fn + 2 – 1 n+1+ Fn + 1Fn + 2 + 1 But.Fa + 2Fa + 3 + 1 2 a+3+ Fa + 2Fa + 3 + 1 2 2 3…. Subsitute. (37 + 38. F F F F 2 a+3 . 24 + 25 + 26. Therefore.b. 2 n+1 n 1 2 3 4 5 F FnFn + 2 + (-1) 1 4 9 25 64 1 4 9 25 64 n Yes. 2 a+2= ( Fa + 3 – Fa + 2) Fa + 3 + 1 2 a+2= F 2 a+2= F 2 a+3= Fa + 2(Fa + 2 + Fa + 3) – 1. 4. Proof by Induction: 2 n 2 First. assume that 1… F n+1= FnFn + 2 – 1 is true for some n that is a positive odd integer. Also True. where a is even. We know that Fn = Fn + 2 – Fn + 1 . F 2 = F1F3 + (-1) => 1 = 1(2) – 1. 2 For n = 2. 1 implies 2. we get 2 n+1= ( Fn + 2 – Fn + 1) Fn + 2 – 1 2 n+1= F 2 n+2= F 2 n+2= Fn + 1(Fn + 1 + Fn + 2) + 1 F F F F 2 2 n+2 . Take the Challenge: 1. Fn + 1 + Fn + 2 = Fn + 3 . so. 2. This is true. 2 n+2= 2…F Fn + 1Fn + 3 + 1. Let n + 1 = a. 10 + 11 + 12 + 13 + 14 + 15. 5.

an = 5n – 3 12. an = 10n – 6 15.4 D. 13 29. 17. an = 14.1. 46 are true. Arithmetic. 37 23. Not Arithmetic 4. 3775 38. . an = 4n – 9. 31. 1220 36. d = 3 3. 8. d = 1 2. 16. 43/5 21. –9/2 19. 210 37. d = ½ 9. Arithmetic. 21 33.2 A. –5 24. 11. 44. Arithmetic. 44 35. d = –4 5. Arithmetic. 21 30. 25. Arithmetic. –1 22. 765 F. Not Arithmetic 7. 76 18. 42. 1. Arithmetic. 46 28. Not Arithmetic B. d = 5 6. Not Arithmetic 8. an = 3n – 6 16. 14 E. an = –3n + 8 13. d = 2/3 10.207 20. 10 32. 16 26.4721 C. 15 27. 96 34.

8. -1. a. -200. 99 19. 579 18. Kulang sa info. Sum = 20. 17. 13. 8. P465 15. 1275 4. Sum = -10100 B. -74. -1400 5. 2. Sum = -1245 4. Sum = 816 2. -27 6. 4. 12. 1. No. 630 cm 11. 400. 7 10.200 6. -65 7. -2. 116. 504 3. 3488 5. 0. 4. 3888 8. 20. b. 88. Sn = = Cancel n on both sides. -4. 18. -85. P7100 14. we get = 3n – 1 2 + an = 6n – 2 an = 6n – 4 2 = 3n – n . 1180 3. and there will be a total of 9 rows. -6. 8. -4. 14. 1. 2. 396 2. y(x + z) = 2xz y(x + z) = 2xz xy + yz = 2xz xy – xz = xz – yz x(y – z) = z(x – y) 16. 2. The last row will contain 3 blocks. 12.Powerplus A. 320 9. 6 13.

1.-1/625 22.Take the Challenge 1. -8. -9. -32. 1. 11. . -25. 2. 2. Not geometric 6. -32 21. 243 16. -16. -16 15. 2. ratio = 1/3 4. 9. -192. 50.3 Warmup Practice A. 32. 19. -9. 5/8 12. Not geometric 5. 5/2. -5. -12. 3125 17. 32. 4. 1250 32. Geometric. b. 40 78 92 166 ( not sure ) 45 SECTION 1. 4. 10. 4b. -8. -64. 12. 8. 2. -1 31. -3. -4 30. Geometric. -32. 27. 81. 24. 33. Geometric. Geometric. ratio = -1/3 7. -81. ¼. 5. 4. 381 35. -728 . . c. 4. 3. 50. 5/4. C. ½ 23. Geometric. -16. -1/125. 4. Geometric. -243 D. 250. -768 26. -625. -16. 3. -1/4. 2. 125. Geometric. Not geometric 9. -81. -4 28. -36. 5. 12. -2. -1. 33 36. . 12. ratio = x/2 B. ratio = 1/b 10. 4/27 13. ratio = -2 8. 5. -4 29. -10. 1250 27. -1/25. ratio = 5 2. 4/3. -3. 8. 2a. -64. 16. 4/9. 3. 3. ratio = 2 3. -27. 8. 6. 48 25. -1. -8. 6. -4 14. 24. -1/16. 18. 2. -64. 48 20. ½. 512 24. -1. 10. -250. 728 34. 27. 128. 3.

831681 m Take the Challenge 1. 55987 41. 39. -85/24 or -3 13/24 E. ½ 15. units 2. this means that T1 . 24. By the difference of squares property. 81. Next. ½ 9.01r. So.01r x T0.134. 1/27 12. Impossible 20. T3 .473. 1/16 2. -1 4. 54. First.01r) . 27 19. 2047 3. 4. 1. 12. 2343/1024 or 2 295/1024 Powerplus A.01r x T0 = T0(1 + 0. 1. r% of T0 = 0. 18. 32. 2. So. -64. First. Tn n form a geometric sequence with common ratio (1 + 0. we know that r% = 0. -54 16. . 8. we have: n have 1 + 9 + 9 + ……. 9 n+1 =3 2n + 2 . 1093 40. -1/125 3.33/32 or 1 31/32 45. Also. 6.144.01r) = T0(1 + 0. -16 18. 48 17.604 or 40951/250 4.let T0 be the starting value of the quantity. we have T2 = T1(1 + 0. 31 44. T2 . ¾ 13. we = -516096 a. 6. 18.37. we know that p = = = 2 b. 5√ B. sq.5 38. -1 5. 26/81 46. 2 √ 8. 3584 10. 163.01r). 62 + √ 6. + 9 = 3. -6. But. = = = . 121 + 7. T1 = T0 + 2 0. we have: = = . the sum of the integers from 1 to p is equal to . Approximately 1286. -3 14. 547 42.01r) and Tn = T0(1 + 0.So. . 28. 1/32 11. Similarly. Also. So.01r) . …. 171 43.

2 410/999 16. 5/6 C.3 1/37 17. r = 1/3 4.9 ) 4.0. a1 = 1. 190 1. No sum 7. 31/99 14. 3 5.1. 4 3. 6. 1.5.9 2. 2 10. 80(1 . 1139 No integral value of x. 20 cm 20. a.9 n 3.4 Warmup Practice A. -1/2 2. 10 cuts (n – 1) . 29/225 18. d5 = 6. 1. d4 = 8. 19. 11. 100(1 – 0. √ 1. 1/3 12. 5/11 15. No sum 4.48.120 cm 21. d3 = 7. 30 cm 22. 8/7 9.9 ) C. d2n = 10 x 0. Section 1. -1/7 B. 24 2. n n b. a. 8/49 8. 24 cm Powerplus A.2. 21/8 B. 1/2 (n – 1) b. 3.2/3 13. d2n – 1 = 8 x 0. 1/4 6.

1/ 79 2. 40 cm b. we have P1P2 = √ P2P3 = 2 P3P4 = 2√ P4P5 = … . 400/3 π cm 2 OPn ) = ½ (½)(OPn ) = ¼ (ln) 2 Section 1. Also. a. We know that since OPnPn + 1 is an isosceles triangle. P1P2 = a cm. 1/3 6. cm b. 3/8. we have P1P2 = √ P2P3 . 1/7. 4/23.) = 50 2 2 l1 + l2 + .P3P4 = ½ a cm b. . Also. 1/22.5 A. 1/35 5. So. a.= 50/4 = 25/2 3. this is a geometric sequence with common ratio 1/√ or √ c. this geometric sequence has common ratio of ½ . 50 cm 2 iii. P2P3 = 2P4P5 = 4P6P7 = … . 5/23. A2 = cm 2 2 c. 5/29 2. Finally.. 1/27. 1/27.2 + 2 cm c. 1/13. A1 + A2 + … = 4(l1 + l2 + . 3/7. s = ¼ or ¾ 2.. 40π cm c.2. So. 1/11. Since QP1R is an isosceles right triangle. 4/33 B. i. 1.a(2 + √ ) cm Take the Challenge 1.. 1/32 4. 5/26. and all the cuts are perpendiculars. a.P2P3 = √ cm. then P1P2 = 2P3P4 = 4P5P6 = … . – 1/18 4. 1. ratio = ½ ii. 1/15 3. So.. 1/31. Not a harmonic sequence 2 √ OPn. OP2 = 5√ cm. we know that OPn + 1 = PnPn + 1 = A1 = ½ (OPn + 1) (PnPn + 1) = ½( 2 √ 2 2 Also. a. 2/23 3. 15/8 mm 4. A1 = 25 cm b.

2. ½. 1/m = a + (n – 1)d => 1 = am + dm(n – 1). we have a – d = 0 or a = d. 0. .(i) 1/b = a + (q – 1)d………… (ii) 1/c = a + (r – 1)d…………. 7. 12/7. ¼. 2 9.12 3. Impossible. First. using the formula to get the (m + n)th term. Now. 1/a = a + (p – 1)d………….) 1/m = a + (n – 1)d = a + (n – 1)a = an => a = 1/mn.1/5. So. 6 and 24 10.2/5. Subtracting the second from the first. we have a + (m + n – 1)d = a + (m + n – 1)a = a(m + n) = So. So.(iii) . 9 and 1 8. this is the (m + n)th term of the arithmetic progression so that it’s reciprocal is the harmonic progression given.Powerplus A. 1/10. . 4. b and c are terms of a harmonic progression. 1/a. ……. since m and n are in a harmonic progression. Therefore. Substituting to any of the equations (both will yield the same result. 6/19 4. 1.. The terms of an arithmetic sequence are 2/5. Let a be the first term in that sequence. then 1/m and 1/n are in an arithmetic progression. Since a. we get 1 – 1 = am – an + dm(n – 1) – dn(m – 1) => 0 = a(m – n) + dmn – dm – dmn + dn => 0 = a(m – n) – d(m – n) => 0 = (a – d)(m – n). 1/5. It is given Take the Challenge 1. the (m + n)th term of the harmonic progression is . We know that m ≠ n. 1/b and 1/c are corresponding terms of an arithmetic progression. Let such an arithmetic progression have a general formula of a + (k – 1)d. 1/5. 1/11 5. but for st the sake of this solution let’s use the 1 equation. 12/25. so. and 1/n = a + ( m – 1)d => 1 = an + dn(m – 1). 1/3. However. 1/8. 12/11. 1/5. taking the reciprocals of each will result in one having an undefined value. . 2/n 6. 2.

6 and 3 4. (v). 11 11.6√ x + 30x . But d ≠ 0. Section 1.6√ y + 45y . 8a 3/2 2 + a + 24a + 32a 1/2 + 16 30. 120 3.54√ y + 27 29. 6 25. 1 12. 5 4 3 2 26. x + 12x y + 60x y + 160x y + 240x y + 192xy + 64y 4 19. y . 3 20. y . 256a + 1024a b + 1792a b 12 11 34. 16 15 31. 5 4 3 2 2 13. x . 28 9.(i) – (ii) gives 1/a – 1/b = a + pd – d – a – qd + d = (p – q)d => (b – a) = (p – q)d x ab……………(iv) (ii) – (iii) gives 1/b – 1/c = a + qd – d – a – rd + d = (q – r)d => (c – b) = (q – r)d x bc………………(v) (iii) – (i) gives 1/c – 1/a = a + rd – d – a – pr + d = (r – p)d => (a – c) = (r – p)d x ac………………. 81+108a +54a +12a +a 4 6 24. 5. x + 8x y + 24x y + 32x y + 16y 6 6 4 16. a 4/3 + 24a 2/3 + 8a + 32a 1/3 + 16 28.(vi) Adding (iv). 105 B. which gives out the desired result. 7 8. c + 10c + 40c + 40c + 80c + 32 6 5 4 2 3 3 2 4 5 15. 20 10. 1.6 A. 27x + 54x y + 36x y + 8y 4 3 2 2 6 4 2 2 4 22.24√ x + 8 6 5 4 3 2 27. 1 5.60√ y + 135y . x + 6x y + 15x y + 20x y + 15x y + 6xy + y 5 4 16 12 8 6 3 2 2 3 4 17. 3. a + 36a + 594a 10 . and (vi) yields (b – a) + (c – b) + (a – c) = (p – q)d x ab + (q – r)d x bc + (r – p)d x ac 0 = d[(p – q)ab + (q – r)bc + (r – p)ac].40√ x + 60x . x + 15x y + 90x y +270x y + 405xy +243y 8 6 5 4 4 4 2 3 2 8 5 4 2 3 3 2 4 23. a + 14a + 91x 26 8 7 6 2 33. 8x – 12x y + 6x y – y 12 5 6 18. 84 7. x + 8x + 28x 14 28 27 32. 2 4. 32x + 96x y + 216x y + 216xy + 81y 21.4y + 6y – 4y + 1 4 2 3 14. 45 6. 6 2. so bc(q – r) + ca(r – p) + ab(p – q) = 0. C.

128a – 2240a + 16800a 93 92 91 2 40. a + 10a b + 45a b 7 5 41. a + 42a b + 861a b 7 6 36. y + . a – 16a b + 112a b 42 41 40 2 39.8 7 6 2 35. a – 14a b + 91a b 8 42. a – 93a b + 4278a b 5 20 18 2 16 4 37. y + 7y + 21y 3 28 26 2 24 4 38.